Biodiversity potential of Nothofagus forests in Tierra del Fuego (Argentina): tool proposal for regional conservation planning - Martínez Pastur, Guillermo José; Peri, Pablo Luis; Soler Esteban, Rosina Matilde; Schindler, Stefan; Lencinas, María Vanessa (Biodiversity and Conservation, 2016)
It is difficult to map and quantify biodiversity at landscape level in areas with low data availability, despite demand from decision-makers. We propose a methodology to determine potential biodiversity pattern using habitat suitability maps of the understory plant species with highest cover and occurrence frequency in the three different forests types of Tierra del Fuego (Argentina). We used a database of vascular plants from 535 surveys from which we identified 35 indicative species. We explored more than 50 potential explanatory variables to develop habitat suitability maps of the indicative species, which were combined to develop a map of the potential biodiversity. Correlation among environmental, topographic and forest landscape variables were discussed, as well as the marginality and the specialization of the indicative species. We detected differences in the niches of the species prevailing in the three forest types. The developed map of potential biodiversity uncovered hotspots of biodiversity in the ecotone of Nothofagus pumilio and N. antarctica as well as in the wettest part of the mixed N. pumilio–N. betuloides forests. It allowed thus to identify forest areas with different conservation potential and can be readily used as a decision support system for conservation and management strategies at different scales including the identification of land-use conflicts (e.g. of biodiversity with timber production and livestock) and the development of a network of protected areas, which currently does not cover the forests of highest conservation value. EEA Santa Cruz Fil: Martínez Pastur, Guillermo José. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Centro Austral de Investigaciones Cientificas. Laboratorio de Recursos Agroforestales; Argentina Fil: Peri, Pablo Luis. Universidad Nacional de la Patagonia Austral; Argentina. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Santa Cruz; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Soler Esteban, Rosina Matilde. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Centro Austral de Investigaciones Cientificas. Laboratorio de Recursos Agroforestales; Argentina Fil: Schindler, Stefan. Universidad de Viena. Department of Conservation Biology, Vegetation & Landscape Ecology; Austria. Environment Agency Austria. Biodiversity & Nature Conservation; Austria Fil: Lencinas, María Vanessa. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Centro Austral de Investigaciones Cientificas. Laboratorio de Recursos Agroforestales; Argentina